Crustal development: Weddel Sea - Ross Sea region. Evolution of the Gondwana plate boundary in the Weddel Sea area - Kristoffersen, Yngve; Hinz, Karl (Geological evolution of Antarctica : proceedings of the Fifth International Symposium on Antarctic Earth Sciences, held at Robinson College, Cambridge, 23-28 August 1987, 1991)
Keywords: Antarktis; Weddellhavet; geofysikk; geologi; seismologi; tektonikk

Geophysical evidence for the East Antarctic plate boundary in the Weddell Sea - Kristoffersen, Yngve; Haugland, Kristen (Nature, 1986)
An improved Gondwanaland reconstruction compatible with geological and geophysical information from the surrounding oceans and continents seems to require microplates to solve the enigmatic pre-early-Mesozoic tectonic relation between West and East Antarctica1. New multi-channel seismic reflection data from the southeastern Weddell Sea acquired during the 1984–85 Norwegian Antarctic Research Expedition (NARE) have outlined a linear WSW–ENE-trending basement ridge buried below the continental slope over a distance of 700 km. This structural high truncates the trend of the large sedimentary basins below the Filchner and Ronne ice shelves and may continue to within a few hundred kilometres of the Antarctic Penninsula. We interpret the basement ridge as part of the East Antarctic plate boundary during the break-up of Gondwana. The morphology and structure of this boundary show greater apparent similarity to a rifted or obliquely rifted margin than to the sheared margin which is predicted by current reconstructions2,3. A linear East Antarctic plate margin extending to the vicinity of the Antarctic Peninsula makes any post-rift micro-plate motion in the Weddell Embayment unlikely.
Keywords: Antarktis; NARE 1984/85; Weddellhavet; geofysikk; geologi; tektonikk

Basic volcanic rocks and tectonic setting. A discussion of the Zr-Ti-Y discrimination diagram and its suitability for classification purposes - Prestvik, Tore (Lithos, 1982)
Keywords: Bouvetøya; forskning; geologi; tektonikk; vulkaner

Morphology of the Weddell Sea and southwest Indian Ocean - Johnson, G Leonard; Vanney, Jean-René; Elverhøi, Anders; LaBrecque, John L (Deutsche Hydrografische Zeitschrift, 1981)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; forskning; geologi; havbunnen; tektonikk